Practical Pedagogic Ideas Teaching Communication Skill: Socializing (Making small talk) (Journal of NELTA, 2018)
English in a real-life situation has become a milestone for the Nepali learners at different levels of their study. Making English contextual and communicative is an essential area to be worked on. This lesson focuses on socializing, where students work on making small talk in English in a new setting.Journal of NELTA ,  Vol. 22, No. 1-2, 2017 December, Page: 127-129